Synthesis, Characterization, and Photocatalytic Activity of Zn-Doped SnO2/Zn2SnO4 Coupled Nanocomposites - Tiekun Jia; Junwei Zhao; Fang Fu; Zhao Deng; Weimin Wang; Zhengyi Fu; Fancheng Meng (International Journal of Photoenergy)
Zn-doped SnO2/Zn2SnO4 nanocomposites were prepared via a two-step hydrothermal synthesis method. The as-prepared samples were characterized by X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), UV-vis diffuse reflection spectroscopy, and adsorption-desorption isotherms. The results of FESEM and TEM showed that the as-prepared Zn-doped SnO2/Zn2SnO4 nanocomposites are composed of numerous nanoparticles with the size ranging from 20 nm to 50 nm. The specific surface area of the as-prepared Zn-doped SnO2/Zn2SnO4 nanocomposites is estimated to be 71.53 m2/g by the Brunauer-Emmett-Teller (BET) method. The photocatalytic activity was evaluated by the degradation of methylene blue (MB), and the resulting showed that Zn-doped SnO2/Zn2SnO4 nanocomposites exhibited excellent photocatalytic activity due to their higher specific surface area and surface charge carrier transfer.